Influence of organizational culture, leadership and rewards on performance of employees in the regional development, research and development planning agency of kerinci regency - Ronal Regen; Ronal Harison Ramli; Windrawadi Windrawadi; Wawan Suswanto (Journal of Educational and Learning Studies, 2021)
This study aims to see the effect of (1) Organizational culture on the performance of Bappedalitbang Kerinci employees (2) Leadership on the performance of Bappedalitbang Kerinci employees (3) Reward for the performance of Bappedalitbang Kerinci employees (4) Organizational culture, leadership and rewards together influence the performance of Bappedalitbang Kerinci employees. The population and sample in this study were all 35 employees of Bappedalitbang Kerinci Regency. The technique of determining the number of samples using total sampling. The data analysis technique used multiple regression by fulfilling the requirements of the classical assumption test of normality, and multicollinearity, heteroscedasticity. The results of this study indicate that (1) Organizational culture has a positive significant effect on the performance of Bappedalitbang Kerinci employees (2) Leadership provide a positive influence on the performance of Bappedalitbang Kerinci employees (3) Rewards have a positive influence on the performance of Bappedalitbang Kerinci employees (4) Organizational culture, leadership and rewards jointly have a positive effect on the performance of Bappedalitbang Kerinci employees.